PENYELESAIAN PERCERAIAN ADAT PADA MASYARAKAT DAYAK BELANGIN DI DESA ENGKADU KECAMATAN NGABANG KABUPATEN LANDAK - NIM. A1011181220, YEHEZKIEL (Fakultas Hukum Universitas Tanjungpura, 2023)
Abstrac The Dayak Belangin Indigenous People are guided by the provisions of customary law that apply as a guide in regulating the social life of their people, one of which is Divorce Customs. Traditional divorce in Engkadu Village, Ngabang District, Landak Regency is still carried out today and has been carried out for generations and passed down from the ancestors of the Belangin Dayak people. At this time there has been a change in customary material in the settlement of customary Dayak Belangin divorces in Engkadu Village, Ngabang District, Landak Regency due to the increasingly advanced development of the people's lives.The formulation of the problem